ANALISIS PERTANGGUNGJAWABAN ALOKASI DANADESA DENGAN PENDEKATAN GOOD GOVERNANCE PADA DESA TALANG BULUH KABUPATEN BANYUASIN - Ghazali, Rosalina; Fahmi, Muhammad; Katiallo, Taufik (Balance : Jurnal Akuntansi dan Bisnis, 2018)
The problem of this research is How the accountability of Village Budget allocated of Talang Buluh VillageinBanyuasin at kecamatan Talang Kelapain 2014, with the approach of Good Governance. The goal is to determinethe accountability report on the allocation of funds Desa of Talang Talang Buluh Banyuasin kecamatan TalangKelapa in 2014, with the approach of Good Governance. The variables used by the village fund allocationapproach with indicators of good governance, transparency, accountability, Efficient, Effective, and Participation.Secondary data with data collection interviews and documentation The analysis showed that yet implementedaccountability Budget Allocation Approach Good Governance by Minister Regulation No. 37 Year 2007 regardingGuidelines for Financial Management in the village of article 22 in the at village of Talang Buluh kecamatanTalang Kelapa regional Banyuasin.